2011
DOI: 10.1093/eurheartj/ehr204
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding in acute coronary syndromes and percutaneous coronary interventions: position paper by the Working Group on Thrombosis of the European Society of Cardiology

Abstract: Bleeding has recently emerged as an important outcome in the management of acute coronary syndromes (ACS), which is relatively frequent compared with ischaemic outcomes and has important implications in terms of prognosis, outcomes, and costs. In particular, there is evidence that patients experiencing major bleeding in the acute phase are at higher risk for death in the following months, although the causal nature of this relation is still debated. This position paper aims to summarize current knowledge regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
187
0
20

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(213 citation statements)
references
References 70 publications
6
187
0
20
Order By: Relevance
“…18 The link between bleeding and poor clinical outcomes is complex and has a mutlifactorial basis. 19 Consistent with previous studies, we found TRA to be a predictor for reduced bleeding and access-site complications. Our data demonstrate that the occurrence of a major bleeding event was associated in increased 1-year mortality, corroborating previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…18 The link between bleeding and poor clinical outcomes is complex and has a mutlifactorial basis. 19 Consistent with previous studies, we found TRA to be a predictor for reduced bleeding and access-site complications. Our data demonstrate that the occurrence of a major bleeding event was associated in increased 1-year mortality, corroborating previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…Current guidelines recommend the use of proton pump inhibitors to prevent adverse GI complications of antiplatelet treatment. 18,19 The emergence of new ADP-receptor antagonists, such as prasugrel and ticagrelor, has challenged the position of clopidogrel. 35,36 However, given the vast experience with clopidogrel and the fact that it is now widely available in its generic form at reduced cost, the use of clopidogrel will prevail for many years.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Currently, the use of proton pump inhibitors is the prevailing strategy for the prevention of GI bleeding during antiplatelet therapy. 18,19 Whether these drugs may reduce the cardiovascular protection by antiplatelet drugs has been discussed, 20 but the randomized COGENT trial showed that in patients treated with aspirin and clopidogrel, proton pump inhibitors reduce GI bleeding complications without increasing cardiovascular event rates. 21 Although bleeding, including GI bleeding, is the most frequent complication of clopidogrel therapy, safety data on the use of clopidogrel obtained from unselected patients are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombotic events may increase mortality from PCI by leading to post-procedural (type 4) MI or stroke. The potential link between bleeding complications and adverse outcomes can be explained not only by the blood loss and organ damage due to hypoperfusion but also -and equally importantly -by the direct effect of blood transfusions with stored red cells and by the discontinuation of antithrombotic therapies in patients who bleed (24). The neutral findings on mortality found in our report therefore can be potentially explained by the divergent effect of different anticoagulation strategies on major bleeding and thrombotic complications -less major bleeding counterbalanced by higher thrombotic rates as with bivalirudin; conversely, potentially less thrombotic events counterbalanced by increased bleeding complications as with otamixaban.…”
Section: Discussionmentioning
confidence: 99%